The Incidence of Heliothrips sylvanus Faure (Thysanoptera: Thripidae) on Table Grapes - Schwartz, A. (South African Journal of Enology and Viticulture, 2017)
Thrips belong to a large group of insects that occur on an extensive variety of plants world wide. Many species of thrips are economic pests that have to be controlled by means of chemical pesticides. They possess piercing mouthparts and usually damage the epidermis of plant parts. Some are vectors of important virus diseases, such as spotted wilt disease in tomatoes which is transmitted by Thrips tabaci Lindeman (Borror, DeLong & Triplehorn, 1976). Several species ofthrips are found on table grape vines in the Western Province of which two are potential economic pests, viz. T. abaci andHeliothrips sylvanus Faure (Schwartz, 1987a). T. tabaci feeds on the very young berries and new shoots, whereas H. sylvanus has a preference for leaves. At present no knowledge exists on the incidence and seasonal occurrence of H. sylvanus on table grapes. As a prerequisite for establishing a practical control program for H. sylvanus, it was deemed necessary to obtain this basic information.